High temperature oxidation resistance of physical vapor deposited Hf-Si-B2±z thin films. (15th August 2022) - Glechner, T.; Bahr, A.; Hahn, R.; Wojcik, T.; Heller, M.; Kirnbauer, A.; Ramm, J.; Kolozsvari, S.; Felfer, P.; Riedl, H.
Abstract: Within physical vapor deposited Hf-Si-B2±z thin films, selective diffusion-driven oxidation of Si is identified to cause outstanding oxidation resistance at temperatures up to 1500 °C. After 60 h at 1200 °C, the initially 2.47 µm thin Hf0.20 Si0.23 B0.57 thin film exhibits a dense oxide scale of only 1.56 µm. The thermally induced decomposition of metastable Hf-Si-B2±z leads not only to the formation of Si precipitates within the remaining thin film (related to a non-homogenous Si distribution after the deposition) but also to pure Si layers on top and bottom of the Hf-Si-B2±z coatings next to the excellent adherend SiO2 based scales. Graphical Abstract: ga1 Highlights: 2.5 µm thin PVD Hf-Si-B2±z coatings withstand long-term oxidation at 1200 °C. Oxide scale thickness of only 1.56 µm after 60 h, 1200 °C for Hf0.20 Si0.23 B0.57 . Single phase structure, but uneven distribution of Si in the as deposited state. Si strongly diffuses out of the Hf-Si-B2±z matrix during oxidation. Stability of the Hf-Si-B2±z coatings proven up to 1500 °C.